2018
DOI: 10.1155/2018/5831278
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bovine Leukemia Virus Antibodies in US Dairy Cattle

Abstract: Objective To estimate current US herd-level and animal-level prevalence of bovine leukemia virus (BLV) in dairy cows and characterize epidemiologic features. Design Cross-sectional observational study design and survey. Animals 4120 dairy cows from 103 commercial dairy herds in 11 states across the US. Procedures Milk samples were collected from dairy cows through routine commercial sampling and tested for anti-BLV antibodies by antibody capture ELISA. Based on the ELISA results of a sample of an average of 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
44
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 28 publications
5
44
0
3
Order By: Relevance
“…Recently, a study looked at the infection rate and found 38% of beef herds, 84% of all dairy herds, and 100% of large-scale dairy herds are infected with the virus [7]. In the USA, incidence of BLV infection has been estimated as high as 94.2% of dairy herds [7,8]. The high prevalence of BLV infection "suggests that the cost of testing and culling of seropositive animals may not be a cost effective method to control the disease" [7.].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study looked at the infection rate and found 38% of beef herds, 84% of all dairy herds, and 100% of large-scale dairy herds are infected with the virus [7]. In the USA, incidence of BLV infection has been estimated as high as 94.2% of dairy herds [7,8]. The high prevalence of BLV infection "suggests that the cost of testing and culling of seropositive animals may not be a cost effective method to control the disease" [7.].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms include swollen lymph nodes, weight loss, decreased milk production, anorexia, and limb paralysis. Roughly 29% of infected cattle [8,12]. Diagnosing BLV infected cattle can be done by simply testing serum for virus-specific antibodies [13].…”
Section: Introductionmentioning
confidence: 99%
“…During pathological processes in the body of a lactating animal, a number of pathogenic microorganisms are released with milk, that can cause serious harm to the consumer (Chaffer et al, 1999). It should also be noted that these microorganisms often have high antibiotic resistance (Hadzevych et al, 2019).…”
mentioning
confidence: 99%
“…One of the most common and dangerous diseases of oncogenic origin among cattle is leukemia (Frie et al, 2017;LaDronka et al, 2018). Bovine leukemia virus is leukemogenic in at least two mammalian species, it is widespread in commercial dairy herds, and can infect a wide range of in vivo hosts and cells, including human cells, in vitro (Ferrer, Kenyon and Gupta, 1981).…”
mentioning
confidence: 99%
See 1 more Smart Citation